Diagnostic and Therapeutic Challenges in Multifocal MRSA Pyomyositis: A Case Report - Tommaso Foggi Viligiardi; Lucia Negro; Alessandro Coppa; Simone Cipani (Case Reports in Critical Care)
Conclusion:Pyomyositis should be considered in immunocompromised patients presenting with localized pain, systemic symptoms, and recent trauma. Early imaging, microbiological confirmation, and multidisciplinary management are critical for improving outcomes.